The Impact of HIIT Training on Developing Specific Endurance and Transitional Speed among First Division Referees in the Iraqi Professional Football League (Journal of the College of Basic Education, 2026)
The study aimed to identify the impact of High-Intensity Interval Training (HIIT) on developing specific endurance and transitional speed among elite Iraqi football referees. Using an experimental approach with a one-group pre-test/post-test design, 12 referees from the Iraq Stars League were selected. The program lasted 8 weeks with 3 sessions per week. Results showed statistically significant differences in favor of the post-test for all physical variables. The study recommends integrating HIIT into the annual training plans for football referees.